Pengaruh Sistem Pengendalian Internal Dan Sistem Informasi Akuntansi Terhadap Pemberian Kredit - Tamsil, Tamsil; Yunus, Rostiaty (Jurnal Unicorn ADPERTISI, 2024)
The purpose of this study is to examine the effect of the internal control system on lending and examine the effect of the accounting information system on lending. The population in this study is employees related to lending, control and finance at PT Bank Negara Indonesia (Persero), Tbk. The sampling technique used in this study uses purposive sampling which is a method of determining samples based on certain scales, or sampling techniques with certain criteria. Based on these criteria, 9 divisions and 6 respondents from each division were determined. Then the total sample is 54 respondents. Research data collection is sourced from questionnaires and research data that has been collected is processed by multiple linear regression analysis. The results of the study found that the internal control system has a positive and significant effect on lending and the accounting information system has a positive and significant effect on lending.